Advances in language and education - McCabe, Anne (Anne M.); O'Donnell, Mick; Whittaker, Rachel (Continuum contemporary studies in linguistics., 2009)
This book examines new functional approaches to language and education, and the impact of these on literacy in the classroom. The first section looks at issues of multimodality, in which the definition of a text is expanded to include not only that which is written down, but also the interaction of writing, graphics, and audiovisual material. The contributors explores ways in which language education can be expanded to deal with multimodal discourse, whether in children's books, in textbooks, or on the web. The second section looks at how critical discourse analysis and appraisal theory can be.